Dwie gwiazdy - Stone, Katherine, 1949- (Warsaw : Amber, 2003)
Polish translation of "Star light, Star bright". Rafe loves both Lily and Brooke but can choose only one. A triangle of a love story.
Keywords: Triangles (Interpersonal relations) -- Fiction; Female friendship -- Fiction; Virginia -- Fiction